Multi-access drug delivery network and stability - Preecha Yupapin; None Mitatha; Narongchai Moongfangklang; None Ma; Nathaporn Suwanpayak; None Ali (My University, 2011)
A novel design of a multi-drug delivery network and diagnosis using a molecular network is proposed. By using a pair of tweezers to generate the intense optical vortices within the PANDA ring resonator, the required molecules (drug volumes) can be trapped and moved dynamically within the molecular bus networks, in which the required drug delivery targets can be achieved within the network. The advantage of the proposed system is that the diagnostic method can be used within a tiny system (thin film device or circuit), which is available as an embedded device for diagnostic use in patients. In practice, the large molecular networks such as ring, star, and bus networks can be integrated to form a large drug delivery system. The channel spacing of the trapped volumes (molecules) within the bus molecular networks can be provided by using the appropriate free spectrum range, which is analyzed and discussed in the terms of crosstalk effects. In this work, crosstalk effects of about 0.1% are noted, which can be neglected and does not affect the network stability.
Keywords: Molecular Junctions and Nanostructures